Relación clima y virosis en los cultivos de trigo y maíz - Gómez Montenegro, Brenda Emiliana; Suarez, F.; Giannini Kurina, Franca; Torrico Ramallo, Ada Karina; Gimenez, Maria De La Paz; Giolitti, Fabian; Balzarini, Monica; Alemandri, Vanina Maria (Universidad Nacional del Noroeste de la Provincia de Buenos Aires -UNNOBA, 2022)
Poster